An Analysis of Grammatical Errors from Indonesian into English in Translating Descriptive Texts - Heni Septina Panjaitan; Kammer Tuahman Sipayung; Winda Damanik; Nova Ulina Tampubolon (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2023)
Translating is such a difficult activity and needs some efforts to master this skill, particularly when it is done by students. This research examines the analysis of grammatical errors in translating texts from Indonesian to English with the aim of being able to answer the following questions: What types of grammar are often misinterpreted by students in interpreting a language? In this field, the method used is descriptive qualitative method and text translation. The data was token from 15 students in one class. The results of the analysis found several errors such as 35 (63.63%) word replacement errors, 15 (27.28%) word omissions, 4 (7.28%) word additions and word rearrangement 1 (100%). In which all errors are found are 261. The most common mistake that occurs is substitution. The use of Past Tenses is one of the causes of students' difficulties in translating descriptive texts. From the results it can be suggested that should be able to teach students how students how to translate texts correctly and provide time or opportunity for students to practice focusing on grammar, especially in using tenses, verbs, articles, auxiliary verbs, noun phrases and pronouns.